PENGARUH PELATIHAN KERJA, LINGKUNGAN KERJA, DAN KOMPENSASI TERHADAP TINGKAT PRODUKTIVITAS KERJA KARYAWAN STUDI KASUS PADA UD. KARYA SEJATERA DESA CAMPURSARI KECAMATAN SAMBIT KABUPATEN PONOROGO - Enggar Lestari; Naning Kristiyana; Dwi Warni Wahyuningsih (Bussman Journal : Indonesian Journal of Business and Management, 2022)
The purpose of this study was to determine the effect of job training, work environment and compensation on the level of employee productivity at UD. Karya Sejatera in Campursari Village. The method used in this study is a quantitative method. The population in this study were all craftsmen with a sample of 40 employees of UD. Karya Sejatera. The results of this study indicate that: 1.) job training has no effect on the work productivity of the UD company. Prosperous Works. The training has not been maximized so that in order to increase productivity, the company must improve training programs with more modern methods so that the resulting productivity also increases 2.) The work environment has a positive and significant effect on UD's work productivity. Karya Sejatera, with a safe, comfortable work environment makes employees feel enthusiastic about working so that work productivity increases. 3.) compensation has a positive and significant effect on UD. Karya Sejatera by paying attention to the salary and compensation of employees makes employees feel satisfied with the rewards of the work they do so they can continue to work at the company 4.) Simultaneously job training, work environment and compensation affect UD's work productivity. Prosperous Works